2021
DOI: 10.3390/app11062572
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Workflow in Design for Additive Manufacturing

Abstract: Additive Manufacturing (AM) brought a revolution in parts design and production. It enables the possibility to obtain objects with complex geometries and to exploit structural optimization algorithms. Nevertheless, AM is far from being a mature technology and advances are still needed from different perspectives. Among these, the literature highlights the need of improving the frameworks that describe the design process and taking full advantage of the possibilities offered by AM. This work aims to propose a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The authors proposed introducing TO, lattice infill optimisation, and generative design in earlier phases of the design process to maximise AM capabilities. Rosso et al [9] presented a DfAM workflow for embodiment design that combines Computer-Aided Design tools for the geometric modelling of the part and Computer-Aided Engineering tools for the optimisation and simulation phases. Their workflow considers the possibility of using size optimisation to obtain lattice structures with optimised beams and TO to obtain optimised organic shapes.…”
Section: Dfam Methodologies and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed introducing TO, lattice infill optimisation, and generative design in earlier phases of the design process to maximise AM capabilities. Rosso et al [9] presented a DfAM workflow for embodiment design that combines Computer-Aided Design tools for the geometric modelling of the part and Computer-Aided Engineering tools for the optimisation and simulation phases. Their workflow considers the possibility of using size optimisation to obtain lattice structures with optimised beams and TO to obtain optimised organic shapes.…”
Section: Dfam Methodologies and Methodsmentioning
confidence: 99%
“…The overall DfAM strategy presented in Figure ?? is the lighthouse for other methods conceived for specific problems and products [1,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the first subsection, the modeling methodology based on NURBS free-form deformation is described; in the second subsection, the size optimization method is briefly explained; in the third subsection, the validation methods through the beam linear structural analysis are described. The case study is a piston rod previously investigated by Rosso et al [54,55]. Figure 1 shows the main dimensions of the test case, highlighting in green the design space that was replaced by lattices.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the stiffness of a compliant system can be modified through the implementation of specific cellular arrays in the flexible parts of the system. Tailoring stiffness has become more relevant with the emergence of modern manufacturing processes such as additive manufacturing techniques, capable of fabricating complex topologies and shapes [72][73][74][75]. Some studies [76][77][78] showed how the stiffness in beams can be customized by using different types of cellular structures while obtaining minimum weight designs.…”
Section: Tailoring Stiffness Via Cellular Materialsmentioning
confidence: 99%